1995
DOI: 10.1038/ng0995-83
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the 180–kD bullous pemphigoid antigen (BPAG2), a hemidesmosomal transmembrane collagen (COL17A1), in generalized atrophic benign epidermolysis bullosa

Abstract: Junctional epidermolysis bullosa (JEB) is a heterogeneous autosomal recessively inherited blistering skin disorder associated with fragility at the dermal-epidermal junction. Characteristic ultrastructural findings in JEB are abnormalities in the hemidesmosome-anchoring filament complexes. These focal attachment structures, which extend from the intracellular compartment of the basal keratinocytes to the underlying basement membrane, have been shown to be hypoplastic or rudimentary in different forms of JEB. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
233
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 349 publications
(241 citation statements)
references
References 26 publications
6
233
0
2
Order By: Relevance
“…The hemidesmosome and the anchoring fibril are also important ultrastructures within the BMZ, which serve to unite the epidermis and dermis [4,23]. Laminin 5 and type XVII collagen are thought to constitute the hemidesmosome [3,20], and type VII collagen is a major component of anchoring fibrils [32]. With immunohistochemical analysis of the present study, the presence of the basement membrane was verified in most regions by type IV collagenpositive reactions.…”
Section: Discussionmentioning
confidence: 84%
“…The hemidesmosome and the anchoring fibril are also important ultrastructures within the BMZ, which serve to unite the epidermis and dermis [4,23]. Laminin 5 and type XVII collagen are thought to constitute the hemidesmosome [3,20], and type VII collagen is a major component of anchoring fibrils [32]. With immunohistochemical analysis of the present study, the presence of the basement membrane was verified in most regions by type IV collagenpositive reactions.…”
Section: Discussionmentioning
confidence: 84%
“…The exact role of BP180 in the formation of hemidesmosomes is not known. However, it seems to be required for their full maturation because the deficiency of BP180 found in patients with Generalized Atrophic Benign Epidermolysis Bullosa is associated with abnormal hemidesmosomes (Jonkman et al, 1995;McGrath et al, 1996). One function of BP180 could be to stabilize the hemidesmosomal complex by providing additional sites for protein interactions such as those with the integrin a6 subunit (Hopkinson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we show that in cells in which BP180 organization has been disrupted, endogenous BP230 nonetheless targets to the cell surface in contact with the substrate. Likewise, it has been shown that in the basal keratinocyte layer of the skin of most, if not all, GABEB patients, BP230 is distributed normally along the site of epidermal interaction with the basement membrane zone, despite the fact that epidermal cells in these patients lack BP180 expression (Jonkman et al, 1995;McGrath et al, 1995;Chavanas et al, 1997). Our data provide some evidence that interaction between the cytoplasmic domain of the ␤4 integrin subunit and the BP230 C-terminal domain, or possibly the N terminus of BP230, can ensure a basal localization of the BP230 molecule even when BP180 fails to polarize in cells.…”
Section: Discussionmentioning
confidence: 99%